2017
DOI: 10.1002/jbmr.3188
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Trabecular Bone Microstructure Did Not Recover at Weight-Bearing Skeletal Sites and Progressively Deteriorated at Non-Weight-Bearing Sites During the Year Following International Space Station Missions

Abstract: Risk for premature osteoporosis is a major health concern in astronauts and cosmonauts; the reversibility of the bone lost at the weight-bearing bone sites is not established, although it is suspected to take longer than the mission length. The bone three-dimensional structure and strength that could be uniquely affected by weightlessness is currently unknown. Our objective is to evaluate bone mass, microarchitecture, and strength of weight-bearing and non-weight-bearing bone in 13 cosmonauts before and for 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(97 citation statements)
references
References 44 publications
6
90
1
Order By: Relevance
“…A cross‐sectional analysis may be influenced by bone loss developing after fracture due to low physical activity. In experimental and clinical studies, unloading (hindlimb suspension) and weightlessness result in a similar bone loss in cortical and trabecular compartments . The strong fracture prediction by Tb.N in both sexes is not explained by different age‐related bone loss in these compartments either.…”
Section: Discussionmentioning
confidence: 95%
“…A cross‐sectional analysis may be influenced by bone loss developing after fracture due to low physical activity. In experimental and clinical studies, unloading (hindlimb suspension) and weightlessness result in a similar bone loss in cortical and trabecular compartments . The strong fracture prediction by Tb.N in both sexes is not explained by different age‐related bone loss in these compartments either.…”
Section: Discussionmentioning
confidence: 95%
“…It may be that in‐flight exercise loads the spine relatively more than the hip. Of note, at both skeletal sites, there is tremendous heterogeneity in the rates of bone loss, as noted . The sources of this heterogeneity are not well understood, but demand further attention to identify which crewmembers may benefit most from pharmacologic therapy to maintain skeletal health.…”
Section: Discussionmentioning
confidence: 99%
“…(3) One approach that overcomes the limitations of DXA-BMD measurements involves the use of three-dimensional (3D) computed tomography (CT) scans, that can be used to measure bone density, geometry, and strength via finite element analysis. (4)(5)(6)(7) A few studies have demonstrated the utility of CT scans for assessing the impact of spaceflight on skeletal health, (8)(9)(10)(11)(12) reporting that hip strength, assessed by CT-based finite element analysis (CT-FEA), declines at approximately twice the rate as hip DXA-BMD. (8) Moreover, there was no correlation between the femoral strength declines and hip DXA-BMD declines, (8) highlighting that DXA-BMD may not be a sufficient surrogate for spaceflight-induced changes in bone strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there was a beneficial effect on airflow obstruction in all the patients treated with lebrikizumab, the effect was greater in patients who had circulating levels of periostin, indicating that periostin is a good biomarker for determining candidates for lebrikizumab treatment (Zhu et al 2017). With regards to mechanical stress, under microgravity, periostin can be utilized as a marker of periosteal metabolism because of the fact that periostin concentration in serum increased transiently along with 15% increase in cortical porosity, which indicates that periostin is a good marker of cortical porosity (Vico et al 2017).…”
Section: Clinical Trials On Periostinmentioning
confidence: 99%